Penatalaksanaan Holistik Paseien Wanita Usia 73 Tahun Dengan Skizofrenia Dan Hipertensi Melalui Pendekatan Kedokteran Keluarga - Muhammad Jundi Nasrullah; Dian Isti Angraini (Medula, 2023)
Schizophrenia is a syndrome characterized by decreased or inability to communicate, impaired reality, cognitive impairment, and difficulty performing daily activities. Hypertension is a persistent condition of systolic blood pressure ≥ 140 mmHg and/or diastolic ≥ 90 mmHg. According to Riskesdas 2018 there are 7.0 per 1,000 Indonesian population suffering from schizophrenia. Meanwhile, the prevalence of hypertension at the age of ≥ 18 years was 34.1%. This case report describes a 73-year-old woman with complaints of difficulty sleeping at night because she still hears whispering voices and accompanied by headaches. Mental status examination revealed perceptual disturbances in the form of auditory hallucinations and thought content disturbances in the form of suspicious delusions. The management provided is in the form of medical and non-medical therapy as a holistic intervention with a family medicine approach. This study is aim to identifying risk factors, clinical problems, and management with a patient-centered and family approach. This study is a case report. Primary data were obtained through anamnesis, physical examination and home visits. Secondary data was obtained from the patient's medical record. The assessment is based on a holistic diagnosis from the beginning, process, and end of the study qualitatively and quantitatively. The results of this study is patient was diagnosed with schizophrenia and hypertension. Limited knowledge of patients and families about the patient's disease is a factor that causes complaints to occur. In addition, dietary patterns in the family that are not suitable are also another factor that causes health problems suffered by patients. Holistic and comprehensive management of patient problems has been carried out by providing counseling to increase the knowledge of the patient's family.